Description of two new genera and five new species of clade K92 from Bahia and Espírito Santo, southeastern Brazil (Arachnida, Opiliones, Gonyleptidae) - Kury, Adriano B.; Bernabé, Tiago (Zootaxa, 2023)
The systematics of gonyleptid harvestmen has recently been undergoing critical changes, especially regarding the Pachylinae and the K92 clade. In a recent cladistic analysis of the latter, the authors refrained from describing some of the detected new species to minimize the bulk of the alpha taxonomy in the manuscript. Herein, as a supplement and following the results of that analysis and the dismantlement of the genus Metagonyleptes Roewer, 1913, the formalization of two genera and five species belonging to clade K92 is proposed. Cajango gen. nov. is described in Caelopyginae based on three new species from southern Bahia State. Titanoleptes gen. nov. is proposed in Sodreaninae to include Metagonyleptes calcar Roewer, 1913, Metagonyleptoides cupidensis Soares & Soares, 1946, and two new species from Espírito Santo State.